RANCANG BANGUN DAN UJI KELAYAKAN PEMBANGKIT LISTRIK TENAGA PICOHYDRO TIPE PROPELLER - Andareas Pangkung; La Ode Musa; Wana Putra; Febryanto Kadang (Politeknik Negeri Ujung Pandang, 2017)
South Sulawesi is an area which has abundant hydro energy. Thus allowing the construction of hydro power plant. According to Perusahaan Listrik Negara (PLN) in 2012, South Sulawesi has 72.22% electrification ratio. It shows that there are 27.78% areas of South Sulawesi which have not supplied by electricity. To overcome this, a pico-scale independent power plant is required. Propeller type of picohydro power plant is one of the hydro power plants that can be used in unsupllied areas . This type of plant requires only 2-10 m head so that it has a wide coverage area usage. Beside that, it is very easy in maintenance and simple in construction. Seeing this, picohydro power plant’s design and proper test is important to do as a solution for the people in an unsupplied area. Based on design and proper test , a hydro power plant with 180 mm diameter turbine tap and 55 mm diameter turbine hub, 4 turbine blades and 7 % as the highest system efficiency is constructed.